Cellulose Nanofiber Production from Banana Rachis - Jirón García, Eddy Gabriel (2020)
Rachis of banana with a33,5±1,2% of cellulose and 15,6±1,1% of lignin was usedas raw material for obtaining cellulose nanofibers by combining chemical and mechanical rupture treatment. The nanocellulose obtained was characterized by infrared spectroscopy, thermal gravimetric analysis, scanning electronic microscopy and transmission electronic microscopy. It is concluded that the chemical treatment removed 51,99% of total lignin, and cellulose fibers with 20-50 μm of diameter were obtained.Besides, the nanofiber obtained after the mechanic rupture had a size of 10-15 nm and a crystallinity index of 64,32%.